Analisis Penerapan Program BERSATU dalam Menanamkan Pendidikan Karakter Peduli Lingkungan di Sekolah Dasar Negeri Gunungsari - Aliyya Putri Riadi; Nurdinah Hanifah; Rana Gustian Nugraha (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study was conducted with the aim of describing the implementation of the BERSATU program in instilling environmental character education at Gunungsari State Elementary School, describing the obstacles during the implementation of the BERSATU program and finally, to find out the students' responses to the activities carried out in the BERSATU program to form environmental care characters. This research is a descriptive qualitative research with a case study approach. The participants or subjects in this study were teachers and students at SDN Gunungsari. The method of data collection is through direct observation to the field, through interviews with school residents and documentation. The data analysis technique uses the data analysis model according to Miles and Huberman, namely data collection, data reduction, data display, and conclusion. The results of research related to the implementation of the united program obtained good results through the implementation of daily picket habituation, SABSIH (Sabtu Bersih), and SILISA (Siapa Lihat Sampah Ambil), conditioning and class hygiene competitions. The obstacles found in the process of implementing the BERSATU program are the low awareness of students towards environmental awareness, inadequate facilities, lack of support from parents of students. The response of students is quite good because most of them have been equipped with awareness from their parents to protect the environment, so they are active and enthusiastic when there is this program. In the future, this program is expected to continue so that environmental care character education can grow well in students, implementing character education by bringing students to a place where they can explore and know the importance of caring for the environment.